Direct aqueous injection of the fluoroacetate anion in potable water for analysis by liquid chromatography tandem mass-spectrometry. Issue 46 (8th November 2018) - Parry, Emily; Willison, Stuart A.
Abstract : Sodium fluoroacetate or Compound 1080 is a rodenticide registered in the United States for use in livestock protection collars. Abstract : Sodium fluoroacetate or Compound 1080 is a rodenticide registered in the United States for use in livestock protection collars. The collars are employed to control predation on herd animals ( i.e., killing of cattle by wolves or coyotes). Sodium fluoroacetate is acutely toxic to humans and has potential to cause mass casualties if used to intentionally contaminate water systems. The U.S. Environmental Protection Agency (EPA) is responsible for characterization and remediation if such an incident occurs in the civilian sector. In support of that goal, EPA has published the Selected Analytical Methods for Remediation and Recovery (SAM) document that provides sampling and analysis methods for many hazardous chemicals such as sodium fluoroacetate. Ideal SAM methods require limited sample preparation steps and utilize widely available equipment to ensure the ability for maximum laboratory participation in a large-scale response. The present paper describes a direct aqueous injection (DAI) method for liquid chromatography/tandem mass spectrometry (LC-MS/MS) analysis of the fluoroacetate anion (FAA) in potable water. Sample preservation and filtration are the only pre-processing steps required. FAA is chromatographically separated on an octylsilane (C8) reversed phase column. Separation is attributed to ion-exchange interactions. Electrospray ionization (ESI) in negative mode and detection by tandem mass spectrometry follow. FAA presence was confirmed by two fragment ions in the correct ratio, and use of a labeled standard allowed for quantitation by isotope dilution. FAA detection and quantitation limits were 0.4 μg L −1 and 2 μg L −1, respectively. Four different drinking water utilities provided water samples from varying locations across the U.S. All the water samples were fortified with FAA and tested to evaluate analyte stability and the robustness of the method.